Preparation method of titanium-doped quartz sand and application of quartz sand
Through high-temperature stirring and mixing of high-purity silicon sol and titanium sol and ultrasonic treatment, a homogeneous titanium-doped silicon gel was formed, which solved the problem of uneven distribution of titanium elements, realized the preparation of high-purity titanium-doped quartz sand, reduced the preparation difficulty, and obtained high-performance low-expanded quartz glass.
Patent Information
- Application Number
- CN202411907253.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
In the existing preparation methods for titanium doped quartz sand, the distribution of titanium elements is uneven, which affects the quality of quartz glass and is difficult to control.
By selecting high-purity silicon sol and titanium sol, stirring and mixing at high temperature, then adjusting the pH value under ultrasonic action, induced to form a homogeneous titanium-doped silicon gel, which was treated by freezing and vacuum drying, and finally obtained titanium-doped quartz sand by multiple calcination.
The uniform distribution of titanium elements is achieved, the control difficulty of the preparation process is reduced, and high-purity titanium-doped quartz sand is obtained, which can prepare low-expanded quartz glass with different performance requirements.
Smart Images

Figure CN119638188A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing quartz sand and applications of the quartz sand, and in particular to a method for preparing titanium-doped quartz sand and applications of the quartz sand. Background Art
[0002] Due to the special requirements of high-end fields such as high-resolution space satellites, the expansion coefficient is 5.7×10 -7 / ℃ quartz glass can no longer meet the demand. When quartz glass is doped with 7%-8% titanium dioxide (TiO2), the expansion coefficient of quartz glass can be effectively reduced. One of the traditional production methods of titanium-doped quartz glass is to melt and cool quartz sand and titanium powder as raw materials. However, quartz sand is a large particle, and it is not easy for titanium to penetrate into the quartz sand during melting, resulting in uneven distribution of titanium in quartz glass, which in turn affects the quality of quartz glass. The patent application with announcement number CN116375315A discloses a method for preparing titanium-doped quartz sand, which is to gasify high-purity silicon-containing chemicals and titanium-containing chemicals and obtain silicon-titanium mixed particles by chemical vapor deposition, and then spray dry and granulate to obtain uniformly mixed silicon-titanium doped large particles, and obtain titanium-doped quartz sand by heat treatment, and then melt the titanium-doped quartz sand in a hydrogen-oxygen flame by gas refining to obtain large-sized bubble-free ultra-low expansion quartz glass ingots. The invention not only avoids the contamination of metal impurities other than titanium caused by using natural quartz sand as raw material, but also avoids the high requirements for equipment and process for sintering titanium-containing silica preforms, and realizes the manufacture of large-sized ultra-low expansion quartz glass ingots without bubble generation.
[0003] The above preparation method prepares quartz glass by preparing quartz sand with titanium distributed inside, which can make the titanium element in the quartz glass evenly distributed. However, it is doped with titanium by vapor deposition. During the vapor deposition process, a slight fluctuation in the air flow will cause uneven deposition, which in turn causes uneven distribution of the titanium element, resulting in extremely high control difficulty. Therefore, it is necessary to redesign a preparation method of titanium-doped quartz sand and the application of quartz sand to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing titanium-doped quartz sand and an application of quartz sand, which can effectively reduce the control difficulty and facilitate production, so as to solve the problem of high control difficulty in the existing preparation method.
[0005] The technical solution of the present invention is: A method for preparing titanium-doped quartz sand, characterized in that it comprises the following steps: S1. Selection of silica sol and titanium sol: Select 6N grade 100-200 mesh silicon powder which is hydrolyzed at 100-120°C under the catalysis of ammonia water to prepare a small-particle alkaline silica sol with an impurity content of <50ppb; select titanium dioxide sol; S2. Under the stirring action of a high-temperature reactor, the silica sol: titanium dioxide sol mass ratio of 40-50:3-4 is mixed, and the mixture is mixed and treated at 100-120° C. for 3-5 hours to obtain a titanium-doped silica mixture; the titanium-doped silica mixture is cooled to 35-45° C. and then taken out and transferred to an ultrasonic reactor, and under the action of ultrasonic stirring, glacial acetic acid is added to adjust the pH value to 6-7, and ultrasonic treatment is performed for 10-30 minutes to induce the titanium-doped silica mixture to gradually gel, thereby obtaining a titanium-doped silica gel; S3. Freeze the titanium-doped silica gel at -30°C to -10°C for 5-10 hours, during which the nano-titanium-doped silica in the titanium-doped silica gel polymerizes to form a micron-sized size; S4. The frozen gel was placed in a vacuum dryer at room temperature and dried under vacuum conditions for 10-15h to evaporate the water therein to obtain titanium-doped silica powder; S5. The titanium-doped silica powder is placed in an atmosphere electric furnace and calcined in an oxygen atmosphere, and the temperature is raised from room temperature to 600-800°C and then kept warm for 2-4h, and then raised to 1000-1100°C and then kept warm for 3-5h, and then cooled to room temperature with the furnace; the water and hydroxyl impurities are further evaporated by calcination, and the impurities are burned by oxygen, thereby removing impurities; S6. After removing impurities, the titanium-doped silica powder is taken out and placed in a vacuum electric furnace at a temperature of 1000-1200° C. and calcined for 5-10 hours to obtain titanium-doped quartz sand.
[0006] In step S1, the average particle size of the silica sol particles is 30-50 nm, and the solid content is 20%-30%. If the silica sol particle size is less than 30 nm, local precipitation is likely to occur when the titanium dioxide sol is added. If the silica sol particle size is greater than 50 nm, flocculent precipitation is likely to occur when the titanium dioxide sol is added.
[0007] The average particle size of the titanium dioxide sol particles in step S1 is 5-20 nm. Preferably, the titanium dioxide sol in step S1 is a nano titanium dioxide sol of model VK-TA33B produced by Zhiti Corporation.
[0008] The vacuum degree during drying in the vacuum dryer in step S4 is 2-10 Pa.
[0009] The oxygen flow rate in step S5 is 5-10 L / min.
[0010] The vacuum degree of the vacuum furnace in step S6 is 1*10 -3 -5*10 -3 Pa.
[0011] The titanium-doped quartz sand prepared in step S6 has a titanium content of 7%-8%.
[0012] An application of titanium-doped quartz sand, characterized in that: the titanium-doped quartz sand is screened, titanium-doped quartz sand with a particle size of 80-240 μm is selected and introduced into a quartz glass burner, and melted into a low-expansion quartz glass ingot by a gas refining method in a hydrogen-oxygen flame.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. Controllable process: The titanium doping ratio can be flexibly controlled. By selecting high-purity raw materials and stirring and mixing them, high-purity titanium-doped quartz sand can be obtained. By adjusting the ratio of silica sol and titanium sol, the titanium doping content can be flexibly adjusted to prepare titanium-doped quartz sand with different performance requirements.
[0014] 2. Uniform titanium doping: Silica sol and titanium sol of different particle sizes are mixed in a certain proportion and according to the grading relationship to obtain a composite silica mixture under heating conditions, and the pH value is adjusted to induce gelation, thereby forming a homogeneous gel, which can achieve uniform distribution of titanium elements; and the mixing process is not easy to be disturbed and the distribution of titanium elements is not easily affected.
[0015] 3. The size of low expansion glass is controllable. Low expansion glass of different sizes can be obtained by gas refining and melting process of titanium-doped quartz sand. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a transmission electron microscope image of the titanium-doped silica gel of the present invention; Figure 2 is a micrograph of the titanium-doped silica powder of the present invention; Figure 3 It is the particle size distribution diagram of the titanium-doped quartz sand of the present invention. DETAILED DESCRIPTION Example 1
[0017] The method for preparing titanium-doped quartz sand comprises the following steps: Select a small-particle alkaline silica sol with an impurity content of 30ppb, an average particle size of 30-50nm, and a solid content of 25%. Select a titanium dioxide sol with an average particle size of 5-20nm. Under the stirring action of a high-temperature reactor, mix the silica sol and titanium dioxide sol at a mass ratio of 50:4, treat at 100°C for 4h, cool naturally, and take out the mixture after the temperature drops to 40°C and transfer it to an ultrasonic reactor. Under the action of ultrasound, add glacial acetic acid to adjust the pH value to 6.5, and treat with ultrasound for 30 minutes to obtain titanium-doped silica gel. Freeze the titanium-doped silica gel at -30°C for 5h. Put the frozen gel into a vacuum dryer and dry it at 2pa for 10h to sublimate the water in it into a gaseous state to obtain titanium-doped silica powder. The titanium-doped silica powder was placed in an atmosphere furnace and calcined in oxygen atmosphere with an oxygen flow rate of 5L / min. The temperature was raised from room temperature to 600℃ and then kept at this temperature for 4h, and then raised to 1000℃ and then kept at this temperature for 3h. The powder was cooled to room temperature with oxygen flowing throughout the process. After cooling, it was taken out and placed in a vacuum electric furnace for calcination. The vacuum degree of the vacuum furnace was 5*10 -3 Pa, the temperature was raised from room temperature to 1200℃ and calcined for 10h to obtain titanium-doped quartz sand.
[0018] The application of the titanium-doped quartz sand comprises the following steps: The titanium-doped quartz sand is screened, and the ones with a size of 80-240 μm are selected and introduced into the quartz glass burner, where they are melted into titanium-doped quartz glass ingots by gas refining in a hydrogen-oxygen flame. Specifically: Fill the silo with titanium-doped quartz sand and preheat the furnace to 1400℃ at a heating rate of 10-20℃ per hour. Raise the base ingot to the bottom of the continuous melting furnace with a hydrogen-oxygen ratio of 2 to 0.9. When the furnace temperature reaches 1400℃, gradually feed the base ingot. At the beginning, the feed rate is 8-15 grams per minute. When the raw material is well melted from the observation hole, increase the feed rate to 20-25 grams per minute in combination with the continued increase in the furnace temperature. Stabilize the furnace temperature and control it at 1700℃. When the raw material is fully melted and fills the molten pool, the upper and middle cross arms of the continuous melting furnace drop, and the melt is gradually pulled out of the molding port to form a quartz glass ingot.
[0019] The quartz glass produced by the above steps has a titanium doping content of 7.78%, a total impurity content of 0.95 μg / g, and a thermal expansion coefficient of 0.45*10 at 20°C to 100°C. -7 / ℃. Example 2
[0020] The method for preparing titanium-doped quartz sand comprises the following steps: Select a small-particle alkaline silica sol with an impurity content of 20ppb, an average particle size of 30-50nm, and a solid content of 20%. Select a titanium dioxide sol with an average particle size of 5-20nm. Under the stirring action of a high-temperature reactor, mix the silica sol and titanium dioxide sol at a mass ratio of 40:3, treat at 120°C for 3h, cool naturally, and take out the mixture after the temperature drops to 45°C and transfer it to an ultrasonic reactor. Under the action of ultrasound, add glacial acetic acid to adjust the pH value to 7.5, and treat with ultrasound for 20 minutes to obtain titanium-doped silica gel. Freeze the titanium-doped silica gel at -10°C for 10h. Put the frozen gel into a vacuum dryer and dry it at 10pa for 10h to sublimate the water in it into a gaseous state to obtain titanium-doped silica powder. The titanium-doped silica powder was placed in an atmosphere furnace and calcined in an oxygen atmosphere with an oxygen flow rate of 10L / min. The temperature was raised from room temperature to 800°C and then kept at this temperature for 2h, then raised to 1100°C and then kept at this temperature for 5h, and then cooled to room temperature with the furnace. Oxygen was passed throughout the process. After cooling, it was taken out and placed in a vacuum electric furnace for calcination. The vacuum degree of the vacuum furnace was 1*10 -3 Pa, heated from room temperature to 1200℃ and calcined for 5h to obtain titanium-doped quartz sand.
[0021] The application of the titanium-doped quartz sand comprises the following steps: The titanium-doped quartz sand is screened, and the ones with a size of 80-240 μm are selected and introduced into the quartz glass burner, where they are melted into titanium-doped quartz glass ingots by gas refining in a hydrogen-oxygen flame. Specifically: Fill the silo with titanium-doped quartz sand and preheat the furnace to 1400℃ at a heating rate of 10-20℃ per hour. Raise the base ingot to the bottom of the continuous melting furnace with a hydrogen-oxygen ratio of 2 to 0.9. When the furnace temperature reaches 1400℃, gradually feed the base ingot. At the beginning, the feed rate is 8-15 grams per minute. When the raw material is well melted from the observation hole, increase the feed rate to 20-25 grams per minute in combination with the continued increase in the furnace temperature. Stabilize the furnace temperature and control it at 1700℃. When the raw material is fully melted and fills the molten pool, the upper and middle cross arms of the continuous melting furnace drop, and the melt is gradually pulled out of the molding port to form a quartz glass ingot.
[0022] The quartz glass produced by the above steps has a titanium doping content of 7.43%, a total impurity content of 0.84 μg / g, and a thermal expansion coefficient of 0.53*10 at 20°C to 100°C. -7 / ℃. Example 3
[0023] The method for preparing titanium-doped quartz sand comprises the following steps: Select a small-particle alkaline silica sol with an impurity content of 50ppb, an average particle size of 30-50nm, and a solid content of 30%. Select a titanium dioxide sol with an average particle size of 5-20nm. Under the stirring action of a high-temperature reactor, mix the silica sol and titanium dioxide sol at a mass ratio of 45:3.2, treat at 100°C for 5h, cool naturally, and take out the mixture after the temperature drops to 35°C and transfer it to an ultrasonic reactor. Under the action of ultrasound, add glacial acetic acid to adjust the pH value to 7, and treat with ultrasound for 10 minutes to obtain titanium-doped silica gel. Freeze the titanium-doped silica gel at -20°C for 7h. Put the frozen gel into a vacuum dryer and dry it at 5pa for 7h to sublimate the water in it into a gaseous state to obtain titanium-doped silica powder. The titanium-doped silica powder was placed in an atmosphere furnace and calcined in an oxygen atmosphere with an oxygen flow rate of 8L / min. The temperature was raised from room temperature to 700°C and then kept at this temperature for 3h, then raised to 1100°C and then kept at this temperature for 4h, and then cooled to room temperature with the furnace. Oxygen was passed throughout the process. After cooling, it was taken out and placed in a vacuum electric furnace for calcination. The vacuum degree of the vacuum furnace was 3*10 -3 Pa, the temperature was raised from room temperature to 1100℃ and calcined for 7h to obtain titanium-doped quartz sand.
[0024] The application of the titanium-doped quartz sand comprises the following steps: The titanium-doped quartz sand is screened, and the ones with a size of 80-240 μm are selected and introduced into the quartz glass burner, where they are melted into titanium-doped quartz glass ingots by gas refining in a hydrogen-oxygen flame. Specifically: Fill the silo with titanium-doped quartz sand and preheat the furnace to 1400℃ at a heating rate of 10-20℃ per hour. Raise the base ingot to the bottom of the continuous melting furnace with a hydrogen-oxygen ratio of 2 to 0.9. When the furnace temperature reaches 1400℃, gradually feed the base ingot. At the beginning, the feed rate is 8-15 grams per minute. When the raw material is well melted from the observation hole, increase the feed rate to 20-25 grams per minute in combination with the continued increase in the furnace temperature. Stabilize the furnace temperature and control it at 1700℃. When the raw material is fully melted and fills the molten pool, the upper and middle cross arms of the continuous melting furnace drop, and the melt is gradually pulled out of the molding port to form a quartz glass ingot.
[0025] The quartz glass produced by the above steps has a titanium doping content of 7.08%, a total impurity content of 0.91 μg / g, and a thermal expansion coefficient of 0.68*10 at 20°C to 100°C. -7 / ℃.
Claims
1. A method for preparing titanium-doped quartz sand, characterized in that: The following steps are involved: S1. Selection of silica sol and titanium sol: Select 6N grade 100-200 mesh silicon powder which is hydrolyzed at 100-120°C under the catalysis of ammonia water to prepare a small-particle alkaline silica sol with an impurity content of <50ppb; select titanium dioxide sol; S2. Under the stirring action of a high-temperature reactor, the silica sol: titanium dioxide sol mass ratio of 40-50:3-4 is mixed, and the mixture is mixed and treated at 100-120° C. for 3-5 hours to obtain a titanium-doped silica mixture; the titanium-doped silica mixture is cooled to 35-45° C. and then taken out and transferred to an ultrasonic reactor, and under the action of ultrasonic stirring, glacial acetic acid is added to adjust the pH value to 6-7, and ultrasonic treatment is performed for 10-30 minutes to induce the titanium-doped silica mixture to gradually gel, thereby obtaining a titanium-doped silica gel; S3. Freeze the titanium-doped silica gel at -30°C to -10°C for 5-10h; S4. The frozen gel was placed in a vacuum dryer and dried under vacuum conditions for 10-15h to evaporate the water therein to obtain titanium-doped silica powder; S5. The titanium-doped silica powder is placed in an atmosphere electric furnace and calcined in an oxygen atmosphere, heated from room temperature to 600-800 ° C and then kept warm for 2-4h, heated to 1000-1100 ° C and then kept warm for 3-5h, and then cooled to room temperature with the furnace; S6. After removing impurities, the titanium-doped silica powder is taken out and placed in a vacuum electric furnace at a temperature of 1000-1200° C. and calcined for 5-10 hours to obtain titanium-doped quartz sand.
2. The method for preparing titanium-doped quartz sand according to claim 1, characterized in that: The average particle size of the silica sol particles in step S1 is 30-50 nm, and the solid content is 20%-30%.
3. The method for preparing titanium-doped quartz sand according to claim 1, characterized in that: The average particle size of the titanium dioxide sol particles in step S1 is 5-20 nm.
4. The method for preparing titanium-doped quartz sand according to claim 1, characterized in that: The vacuum degree during drying in the vacuum dryer in step S4 is 2-10 Pa.
5. The method for preparing titanium-doped quartz sand according to claim 1, characterized in that: The oxygen flow rate in step S5 is 5-10 L / min.
6. The method for preparing titanium-doped quartz sand according to claim 1, characterized in that: The vacuum degree of the vacuum furnace in step S6 is 1*10 -3 -5*10 -3 Pa.
7. The method for preparing titanium-doped quartz sand according to claim 1, characterized in that: The titanium-doped quartz sand prepared in step S6 has a titanium content of 7%-8%.
8. An application of titanium-doped quartz sand, characterized in that: The titanium-doped quartz sand as described in any one of claims 1 to 8 is screened, and the titanium-doped quartz sand with a particle size of 80-240 μm is selected and introduced into a quartz glass burner, and melted into a low-expansion quartz glass ingot by a gas refining method in a hydrogen-oxygen flame.
Citation Information
Patent Citations
Preparation method of titanium-doped synthetic quartz sand
CN116375315A